KEBUTUHAN KARYAWAN PADA UNIT FUNGSIONAL KEBUN PTPN IV MEDAN, SUMATERA UTARA - Wahyu Fikri Radhian; Musa Hubeis; Sadikin Kuswanto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
The objectives of the research were to analyze the employee workload, and calculate the optimum labor at PTPN IV. Work sample was the method used to analyze the workload of the employees, and WISN (Workload Indicator of Staffing Needs) was used to calculate the optimum labor. Through the work sample collection technique of WISN, the analysis of workload and calculation of labor were conducted. The utilization of working time of the plant assistants was 77.5 % for their productive activity, 13.7 % for their personal activity, and 8.3 % for their-non-productive activity. Furthermore, the utilization of working time of the processing technique assistants was 82.1 % for their productive activity, 11.7 % for their personal activity and 6.2 % for their non-productive activity. This shows that the workload for the plant assistants is reasonably high and that for the processing techniques assistants is high. Through the method of WISN, the average calculation results showed that there is an excess of two employees of plants and a shortage of two employees for the processing technique. The managerial implications that can be used as input include the need of the company to conduct a reassessment of the planning of Human Resources of PTPN IV functional unit in terms of recruitment, competency and conducted training.Key words: workload, work sampling, labor requirement, WISN